2015
DOI: 10.4103/2249-4863.152271
|View full text |Cite
|
Sign up to set email alerts
|

Bloody tears: A rare presentation of munchausen syndrome case report and review

Abstract: We report a 16-year-old Jordanian female who presented with bleeding from both eyes of sudden onset. Her physical examination was remarkable for blood pouring from both eyes, and normal otherwise examination including eye and nose examination. During hospital stay, it was noted that “bleeding” occurred only when alone in the room. She later was seen to prick her finger tips of the left hand with her right hand using a hair clip. She denied any psychological problems, and later did not show for follow-up. Munch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…[ 2 ] Literature review revealed many case reports with undetermined source of haemlacria[ 3 4 ] and a female preponderance. [ 5 6 7 8 ] A few patients with undetermined source of haemlacria have been diagnosed with Munchausen syndrome,[ 8 ] whereas nasolacrimal endometriosis has been implicated in a few studies. [ 5 6 ] Ottavay et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Literature review revealed many case reports with undetermined source of haemlacria[ 3 4 ] and a female preponderance. [ 5 6 7 8 ] A few patients with undetermined source of haemlacria have been diagnosed with Munchausen syndrome,[ 8 ] whereas nasolacrimal endometriosis has been implicated in a few studies. [ 5 6 ] Ottavay et al .…”
Section: Discussionmentioning
confidence: 99%
“…The importance of early diagnosis of the Munchausen Syndrome in addition to the patient's benefit from psychotherapy and drug treatment include reduced hospital bed occupancy and prevention of wasting the cost of health care system (8). In this case, a patient with the history of depression is presented with features of Cushing syndrome and medical problems such as uncontrolled hypertension, hyperglycemia, and myopathy in the result of Munchausen Syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The DSM-IV-TR requires that the following three criteria be met for the diagnosis of factitious disorder: (1) intentional production or feigning of physical or psychological signs or symptoms, (2) motivation for the behavior is to assume the sick role, and (3) absence of external incentives for the behavior (such as economic gain, avoiding legal responsibility, or improving physical well-being, as in malingering) [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Factitious disorders are rare: less than 1% of patients [ 1 ]. The criteria for the diagnosis of factitious disorders are found in the Diagnostic and Statistical Manual of Mental Disorders Fourth Edition, Text Revision (DSM-IV TR) [ 2 ]. Isolated subcutaneous limb emphysema secondary to Munchausen syndrome is a rare entity [ 3 , 4 ], and it may have adverse consequences on the limb and patient prognosis, leading to aggressive treatments.…”
Section: Introductionmentioning
confidence: 99%